Interferometria quântica em microcavidades - Caio Olindo de Miranda e Silva Junior (2002)
Nowadays semiconducting cavities are built having thickness less than one micron, some of them filled with absorbing mediums like quantum wells, what lend to them very peculiar properties, mainly in what is referred to their interaction with light. This work is dedicated to the theoretical study, by means of interferometry, of the interaction between photons and empty microcavities, and will serve as a preliminar study for posterior experimental and theoretical works with filled microcavities. We made use of pairs of twin photons generated in type I non-colinear parametric down conversion as ligth source and the Fabry-P´erot cavity of parallel semi-mirrors as a cavity model. We also used the Hong-Ou-Mandel interferometer, puting the microcavity in one of its arms and an optic path compensator device in the other. The strong temporal correlation that exists between the twin photons enables measuring the averaged life time of the photon inside the cavity, that is, the time spent by the photon to cross it.